Avaliação da qualidade da água e análise da percepção do saneamento em um reassentamento urbano coletivo no município de Altamira-PA - PEREIRA, Laize de Lucena (2021)
The impacts caused by large enterprises such as the Belo Monte Hydroelectric are numerous, mainly not that it is concerned with the socio-cultural factors of the populations living in directly affected areas, which as a result of the development and new dynamics that the enterprise brings, has its dynamics changed. In view of this, the present work sought to evaluate the water supply system of the collective urban resettlement São Joaquim, in the municipality of AltamiraPA, a planned neighborhood with access to basic essential services where families were relocated, as well as to correlate with the perception of residents about the sanitation services offered after this relocation. Data were collected on the quality of water available to the resettlement population with the company responsible for the operation of the water supply system, as well as a case study through qualitative research, with a semi- structured questionnaire for their perception. The satisfactory adequate results in all parameters of analysis of water supplies, in all months of study, demonstrating the efficiency of the supply system and adequate quality for consumption, as well as an adequate improvement in the sanitation services offered after the relocation, among the best evidenced was the decrease in waterborne diseases, which shows an improvement in the quality of life of this population in terms of quality of life.